Biocontrol agents of sclerotial blight in tea - Bhagat, Indramani; Chakraborty, Bishwanath (Nepalese Journal of Biosciences, 2013)
One of the important fungal pathogens Sclerotium rolfsii, causing seedling blight disease in tea was found to be predominant in the nursery grown plants. In vitro interaction of S. rolfsii with Trichoderma harzianum and T. viride was studied. Both bioagents inhibited the growth of S. rolfsii.